Tuning the defects in face centered cubic high entropy alloy via temperature-dependent stacking fault energy. (October 2018) - He, Feng; Wang, Zhijun; Wu, Qingfeng; Chen, Da; Yang, Tao; Li, Junjie; Wang, Jincheng; Liu, C.T.; Kai, Ji-jung
Abstract: Extreme-low (even negative) and strong temperature-dependent stacking fault energy (SFE) is one of the most unique properties in face centered cubic (FCC) high entropy alloys (HEAs). Here, by making full use of this unique property, we present a proof-of-principle investigation of tuning defects in FCC HEAs through changing SFE during deformation. A qualitative model is proposed to predict the possibilities of different types of defects in FCC HEAs. Following this model, different defects combinations, instead of individual defects, are well controlled by rolling. FCC HEAs with balanced dislocation, stacking faults and twins show good balance between strength and ductility. Graphical abstract: Unlabelled Image